Abstinence-contingent wage supplements to promote drug abstinence and employment: Post-intervention outcomes. (1st March 2022) - Novak, Matthew D.; Holtyn, August F.; Toegel, Forrest; Leoutsakos, Jeannie-Marie; Silverman, Kenneth
Abstract: Background: Substance use disorder, unemployment, and poverty are interrelated problems that have not been addressed adequately by existing interventions. This study evaluated post-intervention effects of abstinence-contingent wage supplements on drug abstinence and employment. Methods: Unemployed adults enrolled in opioid agonist treatment were randomly assigned to an abstinence-contingent wage supplement group ( n  = 44) or a usual care control group ( n  = 47). All participants could work with an employment specialist throughout a 12-month intervention period. Those in the abstinence-contingent wage supplement group earned stipends for working with the employment specialist and, after gaining employment, abstinence-contingent wage supplements for working in their community job but had to provide opiate- and cocaine-negative urine samples to maximize pay. To assess post-intervention effects of abstinence-contingent wage supplements and compare those effects to during-intervention effects, we analyzed urine samples and self-reports every 3 months during the 12-month intervention and the 12-month post-intervention period. Results: During the intervention, abstinence-contingent wage supplement participants provided significantly more opiate- and cocaine-negative urine samples than usual care control participants; abstinence-contingent wage supplement participants were also significantly more likely to become employed and live out of poverty than usual care participants during intervention. During the post-intervention period, the abstinence-contingent wage supplement and usual care control groups had similar rates of drug abstinence, similar levels of employment, and similar proportions living out of poverty. Conclusions: Long-term delivery of abstinence-contingent wage supplements can promote drug abstinence and employment, but many patients relapse to drug use and cease employment when wage supplements are discontinued. Highlights: Abstinence-contingent wage supplements promoted drug abstinence and employment. Effects of wage supplements did not maintain after intervention was discontinued. Long-term maintenance may require wage supplements to remain in place indefinitely.